Modality - Royes, Sònia Roca (Cambridge : Cambridge University Press, 2023)
This volume guides the reader into the topic of modality, with especial emphasis on the most recent debates. The first part is devoted to modality as a general phenomenon, and the second part is focused on metaphysical modality.
Also issued in print: 2023.
Includes bibliographical references.
Specialized.
Description based on online resource; title from PDF title page (viewed on April 28, 2023).
Keywords: Modality (Logic); Metaphysics